Do self-reported psychosocial working conditions predict low back pain after adjustment for both physical work load and depressive symptoms? A prospective study among female eldercare workers. Issue 8 (17th June 2013) - Clausen, Thomas; Andersen, Lars L; Holtermann, Andreas; Jorgensen, Anette F B; Aust, Birgit; Rugulies, Reiner
Abstract : Objectives: To investigate whether psychosocial working conditions predict the development of low back pain (LBP) in female eldercare workers while adjusting for physical workload and depressive symptoms. Methods: We investigated risk for developing LBP for between 1 and 30 days in the past year and developing LBP for more than 30 days in the past year at follow-up in 1537 female eldercare workers with no LBP in the year before baseline. Data were analysed using logistic regression analysis adjusted for sociodemographic variables, health behaviours, physical workload and depressive symptoms at baseline. Follow-up ranged from 18 to 22 months. Results: High emotional demands, high and medium role conflicts and low influence predicted risk for reporting LBP for between 1 and 30 days in the past year at follow-up after adjustment for sociodemographics, health behaviours and physical workload. All associations became statistically non-significant when adjusted for depressive symptoms. Low and medium influence at work and high emotional demands predicted risk of reporting LBP for more than 30 days in the past year at follow-up, after adjustment for sociodemographics, health behaviours and physical workload. For employees with low (OR 4.16; 95% CI 1.36 to 12.75) and medium (OR 3.93; 95% CI 1.37 to 11.22) influence, this risk remained statistically significant after adjustment for depressive symptoms. Conclusions: Most psychosocial working conditions in this study were no longer associated with risk of LBP after adjustment for depressive symptoms. However, low and medium influence at work predicted risk for LBP for more than 30 days after adjustment for both physical workload and depressive symptoms.